2012
DOI: 10.1080/19439342.2012.710641
|View full text |Cite
|
Sign up to set email alerts
|

Narrative approaches to systematic review and synthesis of evidence for international development policy and practice

Abstract: Thus far, most systematic reviews commissioned to inform international development policy have focused on questions of 'what works', drawing on experimental and quasiexperimental studies of the effects of interventions. This article argues that systematic review methods can be applied to answer a range of different questions for international development and pays particular attention to methods of synthesising qualitative evidence that apply the key principles of systematic reviewing of being comprehensive, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
374
1
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 448 publications
(394 citation statements)
references
References 44 publications
5
374
1
14
Order By: Relevance
“…This does impose limits on the confidence in counterfactual causal mechanisms and explanations for observed phenomena, given that there are multiple determinants of outcomes. 5 Much of the impact evaluation literature now recommends that quantitative evidence built on counterfactual analysis should be combined with qualitative assessments that provide additional information on processes and implementation contexts, in the context of theory--based, mixed--methods approaches to interventions in international development (Snilstveit, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…This does impose limits on the confidence in counterfactual causal mechanisms and explanations for observed phenomena, given that there are multiple determinants of outcomes. 5 Much of the impact evaluation literature now recommends that quantitative evidence built on counterfactual analysis should be combined with qualitative assessments that provide additional information on processes and implementation contexts, in the context of theory--based, mixed--methods approaches to interventions in international development (Snilstveit, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…To identify domains of unmet need across quantitative and qualitative studies we applied a content analytic approach to narrative synthesis [15]: Content categories were determined a priori (based on domains of care need identified and distinguished in previous literature [e.g., 2] including physical, psychological, and informational domains) and study data were parsed and categorised with respect to these categories. For quantitative studies that reported the prevalence of unmet needs by domain, we were able to pool proportions and conduct a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The review is also informed by theory-based impact evaluation (White, 2009), using the theory of change (Figure 1) as the framework for the review, to guide the types of studies included, data collection and analysis. To ensure the review is adequately oriented towards both reporting effects and explaining the reasons for them, we synthesise effects along the causal chain, including qualitative evidence where appropriate, using the effectiveness plus approach (Snilstveit, 2012;Snilstveit et al, 2012). For the quantitative synthesis we use meta-analysis to pool study effects where studies are judged to be sufficiently similar to do so.…”
Section: Methodsmentioning
confidence: 99%